Demography of plains zebras (Equus quagga) under heavy predation. Issue 1 (20th January 2015) - Grange, Sophie; Barnier, Florian; Duncan, Patrick; Gaillard, Jean‐Michel; Valeix, Marion; Ncube, Hlengisizwe; Périquet, Stéphanie; Fritz, Hervé
Abstract: In natural ecosystems, ungulate densities show strong temporal variations. The ecological processes driving these fluctuations are complex: food limitation and predation are both important and can interact. Survival rates are central to this debate, but data are sparse for tropical ecosystems. Here, we estimate age‐ and sex‐specific survival rates for plains zebra in Hwange National Park, a nutrient‐poor savanna with a high predator–prey ratio. We estimated survival from a detailed Capture‐Mark‐Recapture (CMR) monitoring based on 248 individual life histories, for the first time in an African grazer. We controlled for variations in detection probabilities among adult females, which resulted from their social structure. As expected, annual survival was low during the first year (0.441); increased in yearlings (0.560) and peaked at 0.795 and 0.847 in adult males and females respectively. The survival of adult females was lower during the dry season, which probably resulted from higher predation due to predictable movements of zebras to waterholes. Survival at all ages was low compared to ungulates without predators. The demographic model we constructed showed a declining trend ( λ = 0.94), which was consistent with the data from road counts ( λ ^ = 0.92). Life Table Response Experiment (LTRE) analyses using the Serengeti and Kruger populations as references showed that the main cause of this declining trend in the Hwange population was low survival in yearling and adult females; low foal survival also contributed. In this ecosystem, predation is likely to be the main ecological process causing low survival, and therefore a decline in the zebra population.